2012
DOI: 10.1159/000337584
|View full text |Cite
|
Sign up to set email alerts
|

TP-58, a Novel Thienopyridine Derivative, Protects Mice from ConcanavalinA-Induced Hepatitis by Suppressing Inflammation

Abstract: Hepatitis represents a ubiquitous human health problem but effective therapies with limited side effects are still lacking. In this study, we investigated the effect and mechanism of TP-58, a novel thienopyridine derivative, on a murine fulminant hepatitis model induced by concanavalin A (ConA). We found TP-58 markedly alleviated ConA-caused liver injury and increased survival ratio of mice injected with a lethal dose of ConA. Oral administration of TP-58 significantly alleviated ConA-caused liver injury in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Once activated, NF-jB is released from cytoplasm and translocated to nucleus, and where it binds the jB site of target genes and induces the overproduction and release of inflammatory cytokines, which can damage the liver and eventually cause cell necrosis and apoptosis [36]. It has demonstrated that Con A can up-regulate NF-jB expression in liver [37], whereas liver injury induced by Con A is significantly attenuated by inhibiting NF-jB activation [38,39]. Therefore, inhibition of the expression of TLRs and the activation of NF-jB are the effective therapeutic targets for immune-mediated hepatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Once activated, NF-jB is released from cytoplasm and translocated to nucleus, and where it binds the jB site of target genes and induces the overproduction and release of inflammatory cytokines, which can damage the liver and eventually cause cell necrosis and apoptosis [36]. It has demonstrated that Con A can up-regulate NF-jB expression in liver [37], whereas liver injury induced by Con A is significantly attenuated by inhibiting NF-jB activation [38,39]. Therefore, inhibition of the expression of TLRs and the activation of NF-jB are the effective therapeutic targets for immune-mediated hepatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation by LPS, phosphorylation of IκBα activates the NF-κB pathway, which results in NF-kB p65 dissociates from IκBα, then the released NF-κB p65 translocates into the nucleus, and triggers the transcription of related inflammatory genes (Sun and Andersson, 2002 ; Li et al, 2014 ). Some studies have reported that Con A could upregulate NF-kB expression in liver (Tiegs et al, 1998 ), and there was increasing evidence shown that Con A-induced liver injury was significantly attenuated via inhibiting NF-kB activation (Li Y. et al, 2012 ; Song et al, 2013 ). In the present study, the results showed that Baicalin obviously inhibited the protein levels of p-p65, p- IκBα and p65 induced by LPS in liver tissues.…”
Section: Discussionmentioning
confidence: 99%
“…ConA stimulation has been reported to significantly increase TNF-α [25], IL-18 [5], IL-12p70 [26] and MCP-1 [27] in serum, and depletion of these mediators decreases hepatic damage. TNF-α is a proinflammatory cytokine that plays a crucial role in the response to tissue injury, infection, and inflammation [28].…”
Section: Discussionmentioning
confidence: 99%